2019
DOI: 10.3855/jidc.11202
|View full text |Cite
|
Sign up to set email alerts
|

Endocan - a potential diagnostic marker for early onset sepsis in neonates

Abstract: Introduction: Neonatal early onset sepsis assessment is based on the history of pregnancy and delivery and nonspecific clinical signs. None of the biomarkers currently in use for clinical practice has adequate prognostic value, so it is not possible to clearly distinguish neonates with culture-proven sepsis from those with only risk factors or clinical suspicion. Endocan is an endothelial mediator involved in the inflammatory response that is present in low concentrations in the serum of healthy subjects, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…For EOS at a cut-off value of 1.62 ng/mL, the reported sensitivity of serum endocan was 88% and the specificity was 50%. At a higher threshold value of >2.15 ng/mL, specificity improved to 81%, but the sensitivity decreased to 52% [106]. This suggests that currently the clinical utility of endocan as a single marker for the diagnosis of neonatal EOS is limited.…”
Section: Endocanmentioning
confidence: 97%
See 1 more Smart Citation
“…For EOS at a cut-off value of 1.62 ng/mL, the reported sensitivity of serum endocan was 88% and the specificity was 50%. At a higher threshold value of >2.15 ng/mL, specificity improved to 81%, but the sensitivity decreased to 52% [106]. This suggests that currently the clinical utility of endocan as a single marker for the diagnosis of neonatal EOS is limited.…”
Section: Endocanmentioning
confidence: 97%
“…Normally, endocan is localized mainly within the vascular endothelium, the distal tubules of the kidneys and in the lungs, at the level of small veins, arterioles, alveolar capillaries, bronchial epithelial cells and submucosal glands [101]. In healthy subjects, the serum concentration of endocan is low, but the levels are significantly increased in patients with sepsis and are correlated with disease severity [98,[102][103][104][105][106]. Moreover, in newborns without infection, during the first 72 h of life, endocan serum level does not appear to be significantly influenced by sex, delivery method, the presence of meconium in the amniotic fluid, fetal bradycardia/tachycardia or presence of minor birth trauma (ecchymosis, cephalohematoma, clavicle fracture), which have been associated with elevation of CRP and PCT [107].…”
Section: Endocanmentioning
confidence: 99%
“…This situation can be explained by all patients having acute clinical syndromes, giving rise to different changes in laboratory measures. Some patients had chronic coronary syndromes and acute coronary syndromes (in which LDH, CKMB, troponin, and CRP levels increased), chronic heart failure and acute heart failure (with an increase in cardiac enzymes as a result of myocardial injury [23]), VTE (with an increase in D-dimer levels as well as cardiac enzymes [24]), acute inflammatory conditions such as exacerbations of COPD or septic conditions (with an increase in CRP, as well as D-dimer or ferritin [25][26][27][28]), and chronic liver disease (in which LDH, ferritin [29], and D-dimer levels can increase [30]).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a significant decrease of ESM-1 levels in the blood samples taken at the time of discharge compared to the levels at the time of admission. In human neonatal septicemia, Zonda et al (2019) found the level of endocan at the time of admission was significantly higher in septic neonates than in non-septic ones and remained high until the 3 rd day from admission, before returning to their normal values on day 7 (Lassalle et al 1996, Bechard et al 2000, Zonda et al 2019. The findings of the present study suggest that dogs with PVE had high levels of ESM-1 at the time of admission and after the treatment and the resolution of the inflammatory state, while the levels of ESM-1 in the recovered dogs tended to decrease and were comparable with the healthy group.…”
Section: Discussionmentioning
confidence: 99%